E-Community Policing: The Pragmatics of Community Policing on the Profiles Operated by the Hungarian Police - Uricska, Erna; Lippai, Zsolt (Magyar Rendészet, 2024)
Community policing is a philosophy, part of the policing work carried out by the police, whose main aim is to create and maintain public safety. The emergence of social media in policing also led to optimism about the potential of it to transform and improve police-citizen relations. The study introduces the concept of e-community policing, a set of problem identification and solutions generated by communication activities between the two parties in the online sphere. The main questions of the research examine the platforms, methods and tools used by the Hungarian Police to meet these communication challenges. The research observes the interfaces of the organisation’s official website, Instagram profile and Facebook page. The corpus of the research analyses the news items that appeared on all three platforms (n = 28) from the posts of the first month (22 June 2020 – 21 July 2020) (N = 843). The quantitative data of the results show that the platforms share content in line with the expectations of other target groups, and the qualitative data show that social media platforms are trying to respond to the challenges of the information society and to develop a more direct relationship with citizens, both in style and in language.